Villa landscapes in the Roman north
1 online resource (342 pages).
Keywords: This edited volume presents a synthesis of recent research on villas and villa landscapes in the northern provinces of the Roman world. It offers an original, multi-dimensional perspective on the social, economic and cultural functioning of villas within the context of the Roman empire. Themes discussed include the economic basis of villa dominated landscapes, rural slavery, town-country dynamics, the role of monumental burials in villa landscapes, and self-representation and lifestyle of villa owners. This study offers a major contribution to the comparative research of villa landscapes and the phenomenon of regionality in Roman rural landscapes.Amsterdam Archaeological Studies is a series devoted to the study of past human societies from the prehistory up into modern times, primarily based on the study of archaeological remains. The series will include excavation reports of modern fieldwork; studies of categories of material culture; and synthesising studies with broader images of past societies, thereby contributing to the theoretical and methodological debates in archaeology.